An evaluation of the social outreach program of selected RVM tertiary institutions - Penafiel, Maria Gilda Morales, RVM. (Animo Repository, 1994)
This study describes the social outreach program of three tertiary institutions owned and managed by the Congregation of the Religious of the Virgin Mary. A careful study of the documented records and information of each program helped establish a profile description. This was further complemented by interview schedules for administrators and implementors. For the impact of the programs to beneficiaries, a questionnaire developed by Malillin (1983) was used but simplified to suit the study. The five areas included in the improved questionnaire are spiritual/value formation, socio-cultural, educational, health and nutrition and economic upliftment. SWOP analysis was the criteria used to measure the impact of the program to the beneficiaries. The data gathered for this evaluation were treated statistically by simple mean, standard deviation and spreading index. The administrators and implementors confirmed the presence and availability of management aspects of the outreach programs described in table or narrative form following a modified framework of Rondinelli's Project Planning and Management Cycle. This contributed favorably to the success of the programs. Meanwhile, the beneficiaries are unanimous in their opinion as to the positive benefits derived from the services of the outreach programs indicated in the spreading index of four (4) and a mean rating of 1.6. A SWOP analysis further showed strengths of the programs which included services particularly the educational upliftment, the spiritual/value formation and the contribution to economic improvement of the beneficiaries. Weaknesses were not properly outlined owing to high mean ratings. Opportunities included encouraging responses from beneficiaries and positive evaluation from external observers (GO's, NGO's, funding agencies). Cooperation and unity among recipients if not sustained can be a problem in the efficiency and effectiveness of the projects carried out by the programs. Likewise, interests among program implementors particularly students if not sustained will lose all meaning in the main objective of running outreach programs for the poor sectors of the society. The social outreach programs of the three institutions has to be sustained and could be possibly replicated in other schools of the Religious of the Virgin Mary. The administration and the staff of the programs need to sustain the interest of students so they could be actively involved in its services and projects. There is also a need to improve the documentation of the programs. Finally, it is also recommended to encourage students in the graduate school of the institutions to work on research projects about the outreach program of the college to help it improve considerably through feedbacks.